Intercultural Learning and Place‐Based Pedagogy: Is There a Connection?. (5th March 2019) - Reid, Robin E.
Abstract: Place‐based education has the capacity to extend the learning community beyond the parameters of the university and to bring Indigenous and non‐Indigenous, domestic, and international students into the public space and onto the local landscape. By intentionally using place‐based and intercultural pedagogy, this paper draws on student reflections to investigate how intercultural learning occurred through a place‐based assignment.